2022
DOI: 10.3390/membranes12070666
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Diffusion in Alkali-Metal-Doped Polymeric Membranes for Using in Alkaline Direct Alcohol Fuel Cells

Abstract: The alcohol permeability of anion exchange membranes is a crucial property when they are used as a solid electrolyte in alkaline direct alcohol fuel cells and electrolyzers. The membrane is the core component to impede the fuel crossover and allows the ionic transport, and it strongly affects the fuel cell performance. The aim of this work is to compare different anion exchange membranes to be used as an electrolyte in alkaline direct alcohol fuels cells. The alcohol permeability of four commercial anion excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Different types of membranes offer various characteristics and suitability for different applications, leading to the classification of FCs based on their specific membrane technologies. FCs encompass a variety of types, including high-temperature PEM-FCs [24,25], direct methanol FCs [26,27], solid oxide FCs [28,29], alkaline FCs [30,31], microbial FCs [32,33], direct ethanol FCs [34,35], phosphoric acid FCs [36,37], molten carbonate FCs [38], regenerative FCs [39,40], direct alcohol FCs [41,42], enzymatic FCs [43,44], direct ethylene glycol FCs [45], direct carbon FCs [46,47], and more. PEM-FCs are particularly preferred in the automotive sector due to the characteristics of the membrane used in their construction.…”
Section: Principles and Literature Review Of Proton Exchange Membrane...mentioning
confidence: 99%
“…Different types of membranes offer various characteristics and suitability for different applications, leading to the classification of FCs based on their specific membrane technologies. FCs encompass a variety of types, including high-temperature PEM-FCs [24,25], direct methanol FCs [26,27], solid oxide FCs [28,29], alkaline FCs [30,31], microbial FCs [32,33], direct ethanol FCs [34,35], phosphoric acid FCs [36,37], molten carbonate FCs [38], regenerative FCs [39,40], direct alcohol FCs [41,42], enzymatic FCs [43,44], direct ethylene glycol FCs [45], direct carbon FCs [46,47], and more. PEM-FCs are particularly preferred in the automotive sector due to the characteristics of the membrane used in their construction.…”
Section: Principles and Literature Review Of Proton Exchange Membrane...mentioning
confidence: 99%
“…Six of these published papers focus on membranes themselves as a key part of energy conversion systems [ 1 , 2 , 3 , 4 , 5 , 6 ]. The issue of proton-exchange membrane degradation in fuel cells was analyzed by Robert at al.…”
mentioning
confidence: 99%
“…Therefore, the design of new membranes with low alcohol diffusion for these applications is vital. In this context, Fernández-Nieto et al [ 5 ] studied the alcohol diffusion of several anion-exchange membranes doped with different alkaline agents and showed that the membrane structure, type of doping, and type of alcohol affected this crucial property.…”
mentioning
confidence: 99%